2020
DOI: 10.1128/msphere.00981-20
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus 16 (HPV16) E2 Repression of TWIST1 Transcription Is a Potential Mediator of HPV16 Cancer Outcomes

Abstract: HPV16-positive cancers have a better clinical outcome that their non-HPV anatomical counterparts. Furthermore, the presence of HPV16 E2 RNA predicts a better outcome for HPV16-positive tumors; the reasons for this are not known.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 75 publications
0
21
0
Order By: Relevance
“…The HPV E2 protein is essential for viral genome replication, segregation of viral episomes into daughter cells following cell division, and can transcriptionally regulate both virus and host genomes (12, 19, 20). E2 interacts with a variety of host factors to promote progression of the viral life cycle, many of which are essential such as interactions with TopBP1 and BRD4 (12, 19, 23, 53, 58).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The HPV E2 protein is essential for viral genome replication, segregation of viral episomes into daughter cells following cell division, and can transcriptionally regulate both virus and host genomes (12, 19, 20). E2 interacts with a variety of host factors to promote progression of the viral life cycle, many of which are essential such as interactions with TopBP1 and BRD4 (12, 19, 23, 53, 58).…”
Section: Discussionmentioning
confidence: 99%
“…E2 can regulate host transcription in a multitude of ways. We recently reported that E2 can epigenetically repress the TWIST1 at the histone level, inhibiting EMT and promoting a less aggressive cellular phenotype (20). E2 can also promote the recruitment of DNA methyltransferase 1 to interferon response genes, resulting in DNA base methylation and global innate immunity downregulation (21).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations